Demise of Polymerase Chain Reaction/Electrospray Ionization-Mass Spectrometry as an Infectious Diseases Diagnostic Tool. (21st August 2017) - Özenci, Volkan; Patel, Robin; Ullberg, Måns; Strålin, Kristoffer
Abstract : PCR/electrospray ionization-mass spectrometry had been under development for over a decade. It had become commercially available in Europe in 2014 and was under review at the FDA when, in April 2017, its development was discontinued. Abstract: Although there are several US Food and Drug Administration (FDA)-approved/cleared molecular microbiology diagnostics for direct analysis of patient samples, all are single target or panel-based tests. There is no FDA-approved/cleared diagnostic for broad microbial detection. Polymerase chain reaction (PCR)/electrospray ionization-mass spectrometry (PCR/ESI-MS), commercialized as the IRIDICA system (Abbott) and formerly PLEX-ID, had been under development for over a decade and had become CE-marked and commercially available in Europe in 2014. Capable of detecting a large number of microorganisms, it was under review at the FDA when, in April 2017, Abbott discontinued it. This turn of events represents not only the loss of a potential diagnostic tool for infectious diseases but may be a harbinger of similar situations with other emerging and expensive microbial diagnostics, especially genomic tests.